‘We intend to show what Our Lord has done for women’: the Liverpool Church League for Women’s Suffrage, 1913–18 - Cowman, Krista (Studies in church history, 1998)
There was nothing unusual in the inauguration, in December 1909, of a Church League for Women’s Suffrage (CLWS). By January 1914, suffrage had become so expansive that fifty-three organizations competed for or shared a membership divided by tactics, religion, political allegiance, ethnic origin, or metier, but united in their desire to see the parliamentary franchise awarded to women. At the time of the League’s formation, the centre stage of suffrage politics was largely occupied by three groups: the Women’s Social and Political Union (WSPU), suffragettes whose commitment to direct militant tactics brought them spectacularly into both the public eye and the prison cell; the National Union of Women’s Suffrage Societies (NUWSS), whose suffragist members condemned all militancy, describing themselves as ‘law-abiding’; and the Women’s Freedom League (WFL), militants who had quit the WSPU in 1907 in a dispute over constitutional democracy. Whilst they were often virulently opposed to each other, these three groups shared a commitment to an all-female membership and also the political will to prioritize the franchise above the broader feminist issues which adjoined their public campaigns. By contrast smaller suffrage groups, including the Church League, added extra dimensions to the suffrage campaign. They allowed members of the three main groups to explore issues other than suffrage whilst simultaneously providing alternative arenas for suffrage activity to those who did not feel able to commit themselves to the larger bodies. Thus the Church League did restrict its membership to practising Anglicans, but welcomed both militants and constitutionalists, and men as well as women into its ranks. Whilst the achievement of the parliamentary franchise remained its main aim, it also provided space for those who wished to explore ‘the deep religious significance of the women’s movement’. This paper uses the example of the Liverpool branch of the Church League to examine in greater detail to what extent, if any, such explorations resulted in an alteration of the gendered nature of space within Edwardian Anglicanism.